1984
DOI: 10.1002/chin.198427201
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS, PHYSICO‐CHEMICAL PROPERTIES AND PHARMACOLOGICAL STUDIES OF BUDIPINE AND RELATED 4,4‐DIPHENYLPIPERIDINES

Abstract: Nach verschiedenen Verfahren, z.B. aus dem Piperidon (IV), aus den Benzoylpiperidinen (VI) oder durch Alkylierung von (Ia), werden die N‐Alkyl‐diphenylpiperidine (Ib) bis (Id) hergestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The aryl-substituted piperidines have been of particular interest because of their strong interaction with monoamine receptors associated with the central nervous system . There have been some reports of the preparation of aryl-substituted piperidines from piperidones in AlCl 3 −benzene solution, and several reports have appeared in which intramolecular electrophilic aromatic substitution involving piperidones was accomplished with strong Bronsted acids . In this paper, we describe the trifluoromethanesulfonic acid-catalyzed condensations of piperidones and related systems with aromatic compounds to give diarylpiperidines.…”
Section: Introductionmentioning
confidence: 99%
“…The aryl-substituted piperidines have been of particular interest because of their strong interaction with monoamine receptors associated with the central nervous system . There have been some reports of the preparation of aryl-substituted piperidines from piperidones in AlCl 3 −benzene solution, and several reports have appeared in which intramolecular electrophilic aromatic substitution involving piperidones was accomplished with strong Bronsted acids . In this paper, we describe the trifluoromethanesulfonic acid-catalyzed condensations of piperidones and related systems with aromatic compounds to give diarylpiperidines.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are surprisingly few reports concerning the preparation of aryl-substituted piperidines by acid-catalyzed reactions of piperidones with aromatic compounds. 3 Recently, it was shown that diaryl piperidines may be prepared in good to excellent yields by the reaction of piperidones with benzene in the presence of trifluoromethanesulfonic acid. 4,5 We have performed calculations of the TFSA-catalyzed reaction of piperidone with biphenyl and found that the high reactivity of the carbonyl group is due to the inductive effect of a protonated heteroatom rather than through-space electrostatic effects.…”
mentioning
confidence: 99%